Increasing rates of early-onset Luminal A breast cancers correlate with binge drinking patterns - Jianjiu Chen; Rebecca Kehm; Wan Yang; Mary Beth Terry (Breast Cancer Research)
Abstract Background Breast cancer (BC) rates have been increasing in young women in the U.S. Alcohol is an established risk factor for breast cancer and has been consistently associated with hormone receptor positive cancers, the type of breast cancer that has been increasing the fastest in young women. Given these trends, we conducted an ecological study to examine whether alcohol consumption, and specifically binge drinking trends, were correlated with female breast cancer diagnosed under 40 years of age using breast cancer data from the Surveillance, Epidemiology, and End Results (SEER) Cancer Registry. We accounted for a latent period before cancer diagnosis by using exposure 10 years before the outcome (lag model); we also conducted a separate cumulative analysis of 10-year aggregate exposure. Findings Moderate (Incidence Rate Ratio (IRR) = 1.05, 95% Confidence Interval (CI) = 1.02–1.07) and heavy (IRR = 1.05, 95% CI = 1.02–1.07)(≥ 1 and ≥ 2 drinks/day, respectively) alcohol consumption were each associated with Luminal A breast cancer but not the other molecular subtypes. Binge drinking was associated with an increased rate of early-onset Luminal A BC in both the 10-year lag model (IRR = 1.06, 95% CI = 1.02 to 1.11) and the cumulative model (IRR = 1.05, 95% CI = 1.02–1.07). Binge drinking was also associated with early-onset Luminal B BC in the cumulative model (IRR = 1.04, 95% CI = 1.01–1.07), but not associated with ERBB2-enriched or triple negative early-onset BC in either model. Conclusion These trends support the hypothesis that one reason for the increase in early-onset breast cancer is from increased alcohol intake including binge drinking.